Analisis Kritis Penerapan Pendidikan Karakter di Indonesia: Analisis Ontologis, Epistemologis, dan Aksiologis - Wijaya, Hendri; Asyhar, Rayandra; Asrial, Asrial; Syaiful, Syaiful (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to conduct a critical analysis of the implementation of Character Education Strengthening (PPK) in Indonesia from the perspective of ontological, epistemological, and axiological philosophy of science. The research method uses library research with a qualitative approach and employs critical philosophical analysis (philosophical inquiry and critical analysis) and academic literature. The study's results found that ontologically, the essence of PPK is an integral effort to internalize moral dispositions rooted in cultural values and Pancasila. Epistemologically, there are critical challenges in the acquisition and verification of character knowledge; dominant quantitative measurements often fail to capture the internal affective dimension authentically, which leads to methodological inconsistencies in the field. Axiologically, the primary value of PPK is the development of ethical and moral citizens with a national identity, as reflected in the vision of the Pancasila student profile. The conclusion is that although PPK has a solid philosophical and axiological foundation, the biggest challenge lies in the epistemological aspect. Therefore, it is necessary to strengthen the epistemological framework through the development of authentic and consistent qualitative assessment methods, as well as ongoing professional development for teachers. Keywords: Axiology, Epistemology, Philosophy of Science, Ontology, Character Education (PPK), Pancasila Student Profile